Form, Space and Meaning of Traditional Architecture of Towani Tolotang Traditional Community Amparita Sidenreng Rappang - Sani, Andy Sandra; Wikantari, Ria; Harisah, Afifah (ASTONJADRO, 2024)
The Towani Tolotang traditional community, which has traditional Bugis houses, is known for having houses with rounded pillars malibu lenrong, many squares and does not use glass as a window ornament so that it has a distinctive shape. When observing their way of life, the belief in Pengderreng or ade’ customs' greatly influenced the Towani Tolotang Indigenous Community's way of life, also affecting the Towani Tolotang Indigenous Community's view of the world or cosmo, which in turn will influence the meaning of the architecture of their house. The problem in this study is how the relationship between form, space and meaning in the Towani Tolotang traditional house and the influence of cosmology on its form and space. The purpose of this study was to identify the relationship between form, space and meaning and the influence of cosmology on the form and space of the Traditional Architecture of the Towani Tolotang Indigenous Community by using descriptive analysis. While data collection was done by interview and photo methods. The results of this study show that there are differences between the Uwwata, uwak and to sama houses, the Uwwata house is bigger than the uwwa house, has a tapping makampar and is on the watang pola. Main body of the house and Bola is not there or the house next door does not have a chair and table in the living room like the Bugis house in general, the watang pola and the siwali bola unite. The Outer Tapping is a place to receive guests who convey good news, while guests who go straight inside and sit on the inner tapping mean they are delivering sad news. Uwak has a long tapping on the body of the house while the house for to sama, some has tapping and some doesn't have tapping, short tapping is on the body of the house and has a living room in terms of the meaning of Towani Tolotang Architecture which still maintains its customs and sacred rituals Mappenre nanre, tudang sipulung, massarapo and Attorioloang led by Uwatta and Uwak.